Analysis of turbulent flow and thermal structures in low-Prandtl number buoyant flows using direct numerical simulations. (15th June 2022) - Bhushan, S.; Elmellouki, M.; Walters, D.K.; Hassan, Y.A.; Merzari, E.; Obabko, A.
Highlights: DNS database for low- Pr flows involving mixed aiding and opposing buoyant flow conditions. Effect of Re, Pr, and buoyancy on the turbulent flow field and thermal transport. Effect of Re, Pr and Ri on turbulent Prandtl number, and assessment analytic formulations. Abstract: A direct numerical simulation (DNS) database is presented for turbulent flow and heat transfer in a vertical channel for Reynolds number Reτ  = 150 and 640, Prandtl number Pr  = 0.004, 0.025 and 0.71, with and without buoyancy forcing ( Ri  = 0 and 0.15 or 0.21). The effects of Pr on mean and turbulent flow and thermal transport in mixed convective conditions are discussed. Aiding/opposing buoyant conditions result in acceleration/deceleration of mean flow and reduction/enhancement of turbulence. Flow turbulence is highly anisotropic and dominated by the streamwise component on the aiding side, and becomes two-dimensional on the opposing side with a decrease in Pr . Temperature distributions depend on the relative role of molecular and turbulent thermal transport. The former increases with decreasing Pr and the latter with increasing Re . Buoyancy affects thermal transport through augmentation of the wall-normal turbulent heat flux, v ′ θ ′ ¯, which is more pronounced for higher Pr. A priori analysis of the DNS datasets shows that a variable formulation for turbulent Prandtl number in Reynolds-averaged Navier-Stokes simulations performs well for both high- and low- Pr flows without buoyancy and in stable convective regimes, but yields relatively high error in unstable convective regimes.